Host Plants Association with Longhorn Beetles of Food Value: Traditional Knowledge of the Guaraní as Cultural Identity Keepers - Jorge Justino Araujo; Héctor Alejandro Keller; Norma Inés Hilgert (Ethnobiology Letters, 2021)
The study of plant-insect interactions and how cultural groups perceive and manage them constitutes one of the interests of ethnoentomology. This work describes the association between host plants and longhorn beetles (Order: Coleoptera; Family: Cerambycidae), an important food among the Guaraní peoples of the province of Misiones, Argentina. Different management methods of host tree species are analyzed in order to promote the rearing of larvae for edible use. We also discuss a story about the mythical origin of cerambicids relayed by the Ava Chiripa Guaraní community. We reflect on the importance of the local worldview in the maintenance of ancestral practices, such as the cultural tasks involved in slash-and-burn agriculture and the intimate knowledge of biological relationships between the cerambycids and their woody host plants.